Provision of Technical Effectiveness Jelly In Cath Installation By Nurse On The Level Catheterization Urine Pain In Patients In Hospital Care Space Dr. R. Ismoyo Kendari - Budiono Budiono; Sumirah Budi Pertami (Jurnal Keperawatan, 2014)
Action catheterization is invasive and can cause pain, so if done in the wrong way will cause permanent damage to the urethra. Pain is the main complaint that is often experienced by patients with catheterization because of the actions insert a catheter into the bladder hose has a risk of infection or trauma to the urethra. This study aims at providing technical effectiveness jelly Knowing the catheter by a nurse on the level of pain in patients with urinary catheterization in a hospital 2013.Variabel Kendari year in this study are freely giving techniques jelly on the catheter consists of a jelly that is applied to the tip catheter and jelly sprayed directly on the meatus uretra.Variabel dependent in this study was the level of pain. This research is case control, by taking on the primary data on the effectiveness of the use of catheters and jelly on the level of pain after doing catheter respondents through the questionnaire. The population in this study were all patients who will be paired catheters. The samples in this study were nurses on duty in the hospital ward Ismoyo Kendari who perform catheter as many as 10 people and all the patients who will be the installation of a catheter. Sample size in this study as many as 20 people. The samples were taken by non-random sampling with accidental sampling technique. Data processing was performed using univariate and bivariate analysis were then presented in tabular form, followed by an explanation narasi.Hasil and conclusions in this research that there are methods of giving jelly smeared obtained by moderate and severe levels of pain respectively by 5 people (25.0 %) while for the method of administration by way of lubrication jelly or sprayed directly on urethral meatus obtained mild pain levels by 6 people (30%) and were as much as 4 people (20.0%) and technical provision of jelly that is sprayed on the urethral meatus is more effective against decreased levels of pain compared to administration of jelly that is applied to the tip of the catheter in patients with urinary catheterization. The advice can be given that researchers are expected to nursing personnel should use the jelly lubrication by entering into the urethra (lubrication method) because this can cause the sensation of pain with a lighter intensity and speed of installation is faster than on the way jelly stain on edge catheter. Keywords: Jelly Provision, Installation Catheter, Pain Levels